The role of ALDH2 rs671 polymorphism and C-reactive protein in the phenotypes of male ALS patients - Huang, Lifang; Liu, Mao; Tang, Jiahui; Gong, Zhenxiang; Li, Zehui; Yang, Yuan; Zhang, Min (Frontiers in Neuroscience, 2024)
BackgroundThe aldehyde dehydrogenase 2 (ALDH2) rs671 (A) allele has been implicated in neurodegeneration, potentially through oxidative and inflammatory pathways. The study aims to investigate the effects of the ALDH2 rs671 (A) allele and high sensitivity C-reactive protein (hs-CRP) on the clinical phenotypes of amyotrophic lateral sclerosis (ALS) in male and female patients.MethodsClinical data and ALDH2 rs671 genotype of 143 ALS patients, including 85 males and 58 females, were collected from January 2018 to December 2022. All patients underwent assessment using the Chinese version of the Edinburgh Cognitive and Behavioral ALS Screen (ECAS). Complete blood count and metabolic profiles were measured. Clinical and laboratory parameters were compared between carriers and non-carriers of the rs671 (A) allele in males and females, respectively. The significant parameters and rs671 (A) Allele were included in multivariate linear regression models to identify potential contributors to motor and cognitive impairment. Mediation analysis was employed to evaluate any mediation effects.ResultsMale patients carrying rs671 (A) allele exhibited higher levels of hs-CRP than non-carriers (1.70 mg/L vs. 0.50 mg/L, p = 0.006). The rs671 (A) allele was identified as an independent risk factor for faster disease progression only in male patients (β = 0.274, 95% CI = 0.048−0.499, p = 0.018). The effect of the rs671 (A) allele on the executive function in male patients was fully mediated by hs-CRP (Indirect effect = −1.790, 95% CI = −4.555−−0.225). No effects of the rs671 (A) allele or hs-CRP were observed in female ALS patients. The effects of the ALDH2 rs671 (A) allele and the mediating role of hs-CRP in male patients remained significant in the sensitivity analyses.ConclusionThe ALDH2 rs671 (A) allele contributed to faster disease progression and hs-CRP mediated cognitive impairment in male ALS patients.